Teachers’ self-efficacy in dealing with bullying among secondary school students / Lee Jun Choi - Lee, Jun Choi (2013)
Evidences from a number of studies suggest that generally teachers are not very effective when they address or deal with cases of bullying in schools. Although there are now quite a lot of literatures on how or what schools can do in dealing with cases of bullying, curiously enough there is little information available about what teachers actually feel, think, and do when bullying is going on at their schools. Scant attention has been paid to teachers’ self-efficacy regarding bullying and what actually are their ability when they deal with this type of problem, particularly in Malaysia. There also relatively little is known about sources that have an impact on teacher self-efficacy regarding dealing with bullying in school, in the local context or probably in the international arena. The source of influence is predicted to be from behaviour factors (i.e. mastery experience); environmental factors (i.e. vicarious experience, verbal persuasion, and contextual climate) and personal factors (i.e. demographic information, and psychological arousal.) The first purpose of this study was to identify what are the levels of in-service teachers’ self-efficacy in terms of dealing with bullying in secondary schools. The second purpose of this study was to identify whether there is any significant difference in the level of teacher self-efficacy in dealing with bullying according to (a) post they are holding (i.e. senior assistant teachers, discipline teachers, counseling teachers, academic teachers), and (b) gender . The third purpose of this study was to identify the overall source of influence that contributes to teacher self-efficacy among in-service teachers regarding dealing with bullying in secondary school. The fourth purpose of this study was to identify which of the following influences (i.e. mastery experience, vicarious experience, verbal persuasion, physiological arousal, contextual climate, demographic information) are significant predictors of teacher self-efficacy in dealing with bullying. This quantitative research utilizes a correlation method in order to examine the relationship between various sources of influence and xv teacher sense of efficacy when dealing with bullying among students in secondary schools. The measurement for sources of influence on teacher self-efficacy scale in dealing with bullying and the measurement of teacher self-efficacy level when dealing with bullying in secondary school are validated through self-constructed questionnaire. Based on the finding of this study, the levels of teachers’ self-efficacy in terms of dealing with bullying in secondary school among in-service teachers was moderately high (M = 3.83, SD= 0.79). This implies that majority of the in-service teachers were somewhat confident of themselves in having the ability to successfully perform their duty or responsibility in dealing with bullying among students in secondary school. This study also found that there was a significant difference [ F(3, 1916) = 52.416, p < .001, α = .05) ] in the level of teacher self-efficacy in dealing with bullying according to the post they are holding, whereby senior assistants yielded the highest overall mean score of 4.13 (SD=0.77) and academic teachers have the lowest of them all with overall mean score of 3.53 (SD=0.79). Based on the standardized regression coefficients (βs) indices of direct effects of each predictor variable on teacher self-efficacy in dealing with bullying among students, Mastery Experience contributed the highest direct effect or influence on teacher self-efficacy in dealing with bullying among students, followed by Verbal Persuasion and Contextual Climate. Although there is no documented record of local research that examine the sources of influence on teacher self-efficacy in dealing with bullying among students, one clear finding that arises from this study is that, mastery experience and verbal persuasion are prominent predictors of teacher self-efficacy in dealing with bullying among students in secondary schools. In addition, the interrelated and mediating roles of these two efficacy sources indicate that, to some extent, they function interdependently as in-service teachers gain new ways or maybe new skills in relation to deal with various bullying cases among students in secondary schools. It is recommended that teacher xvi preparation or teacher developmental programs regarding the issue of bullying among students in secondary schools, explicitly address these two influences with specific types of training and educational experiences that focus on mastery building through cognitive and meta cognitive strategies, cultivating self-regulation competencies, and establishing a social support system. Such strategies may offer useful treatment ingredients aimed at modifying self-efficacy in dealing with bullying among students, among in-service teachers in secondary schools. As noted earlier, the findings of this study showed that mastery experience consistently remained a crucial source of influence on teacher self-efficacy in dealing with bullying among students. Therefore, training for teachers as well as in-house training for in-service teachers, should focus on acquiring self-regulatory competence so that teachers are able to monitor their own performances. This would provide an important mastery building opportunity for self-efficacy enhancement.